1992
DOI: 10.1111/j.1754-4505.1992.tb00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative hemodynamic changes in ischemic heart disease patients undergoing dental treatment

Abstract: Twenty patients with stable ischemic heart disease in functional capacity Class II-IV underwent dental treatment. Scaling was performed in seven patients without local anesthesia. In the remaining 13 patients, pain control for restoration placement was obtained by local anesthesia: in seven patients, the anesthetics contained epinephrine, while in six this drug was omitted. Heart rate, blood pressure, and electrocardiograph were continuously monitored during the dental session. All patients had elevated systol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
2
6
0
4
Order By: Relevance
“…Davenport et al 6 studied the hemodynamic effects of moderate doses of epinephrine during periodontal surgery in patients with stable cardiovascular disease and found no significant changes in HR or blood pressure, despite the elevation of the plasma epinephrine concentration. In contrast, Leviner et al 4 reported that local anesthesia without vasoconstrictor should be preferred for use in severely compromised patients. However, detailed cardiac functions were not measured in any of these previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…Davenport et al 6 studied the hemodynamic effects of moderate doses of epinephrine during periodontal surgery in patients with stable cardiovascular disease and found no significant changes in HR or blood pressure, despite the elevation of the plasma epinephrine concentration. In contrast, Leviner et al 4 reported that local anesthesia without vasoconstrictor should be preferred for use in severely compromised patients. However, detailed cardiac functions were not measured in any of these previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…25 Increased pressure in cerebral ves-sels may lead to hemorrhage or cerebrovascular accident, while increased renal vascular pressure may lead to kidney failure. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Hypertension is not diagnosed following a single elevated blood pressure reading; however, an elevated reading on one or multiple occasions may be cause for evaluation by the patient's physician. Similarly, diagnosed hypertensive patients may be monitored routinely for assessment of blood pressure control.…”
Section: Annals Of Periodontology Anesthetic Agentsmentioning
confidence: 99%
“…Prevalence of diabetes and impaired glucose tolerance and plasma glucose levels in U.S. population aged20-74 years. Diabetes 1987;36:523-534.…”
mentioning
confidence: 99%
“…Most human studies examining hemodynamic variables after dental injection of 1.8 to 5.4 milliliters of 2 percent lidocaine with 1:100,000 epinephrine have found no significant changes in mean arterial pressure, blood pressure or heart rate in healthy patients or in those with mild-tomoderate cardiovascular disease. 16,19,21,22 So it is recommended that patients with mild-to-moderate cardiovascular disease receive the smallest amount of local anesthetic needed to provide profound anesthesia, with aspiration performed to prevent intravascular injection. Researchers have suggested that the use of conscious sedation to decrease stress and therefore minimize endogenous release of epinephrine may be a more important factor in ensuring hemodynamic stability in patients with cardiovascular disease than are attempts to avoid the small amount of epinephrine used in local anesthetic injections.…”
Section: Dental Management Of Patients With Cardiovascular Diseasementioning
confidence: 99%
“…Ischemic heart disease, most commonly manifested as angina or myocardial infarction, is the major cause of sudden death in the United States. 16,22,24 It usually is caused by decreased coronary blood flow, increased myocardial oxygen demand or both. There are three types of angina: stable, unstable and variant (Prinzmetal's angina).…”
Section: Dental Management Of Patients With Cardiovascular Diseasementioning
confidence: 99%